2017
DOI: 10.1038/s41598-017-12726-4
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus modifies host behaviour through a snake-toxin like region of its glycoprotein that inhibits neurotransmitter receptors in the CNS

Abstract: Rabies virus induces drastic behaviour modifications in infected hosts. The mechanisms used to achieve these changes in the host are not known. The main finding of this study is that a region in the rabies virus glycoprotein, with homologies to snake toxins, has the ability to alter behaviour in animals through inhibition of nicotinic acetylcholine receptors present in the central nervous system. This finding provides a novel aspect to virus receptor interaction and host manipulation by pathogens in general. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 33 publications
4
56
1
1
Order By: Relevance
“…This olfactory infection route scheme [18] has been recently extended to Covid-19 infection [2,11]. To further investigate the molecular aspects of Covid-19 propagation in the brain and its pharmacology, we have been aided by abundant studies on rabies virus (RABV) a negative polarity, single-strand RNA virus that is distinct from the coronaviruses [18][19][20]. nAChRs were shown to be the first receptors for RABV [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This olfactory infection route scheme [18] has been recently extended to Covid-19 infection [2,11]. To further investigate the molecular aspects of Covid-19 propagation in the brain and its pharmacology, we have been aided by abundant studies on rabies virus (RABV) a negative polarity, single-strand RNA virus that is distinct from the coronaviruses [18][19][20]. nAChRs were shown to be the first receptors for RABV [21].…”
mentioning
confidence: 99%
“…nAChRs were shown to be the first receptors for RABV [21]. Structural studies further revealed that a short region in the ectodomain of the rabies virus glycoprotein shows sequence similarity to some snake toxins [20,22] that were initially used to isolate the nAChR from fish electric organs [23]. These snake toxins [24] are known to bind with high affinity and exquisite selectivity to the peripheral muscle receptor, while also to some brain receptors [25,26].…”
mentioning
confidence: 99%
“…T his olfactory infection route scheme [18] has been recently extended to Covid-19 infection [2,11]. T o further investigate the molecular aspects of Covid-19 propagation in the brain and its pharmacology, we have been aided by abundant studies on rabies virus (RABV) a negative polarity, single-strand RNA virus that is distinct from the coronaviruses [18][19][20]. nAChRs were shown to be the first receptors for RABV [21].…”
mentioning
confidence: 99%
“…In addition, answers from this survey indicated that hunting dogs would often chase wild dogs when an encounter did occur. Assuming an infection of rabies in the Australian wild dog population, which is known to induce severe aggressive behavioural changes in the host, such an encounter between a hunting dog and an infected wild dog might result in disease transmission through biting. In contrast to the results of this study, a previous survey of Australian hunters reported a high proportion (17%) of interviewed hunters who had witnessed attacks from wild dogs with their hunting dogs .…”
Section: Discussionmentioning
confidence: 99%